Social responsibility and accountability of Honeysweet Bakeshop - Abordo, Rhea Joy C.
This study, entitled "Social Responsibility and Accountability of HONEYSWEET Bakeshop" focuses on how management of HONEYSWEET Bakeshop practices Social Responsibility and Accountability. It aims to (1) find out how the management of HONEYSWEET Bakeshop view social Responsibility and Accountability, (2) identify the ways in which Social Responsibility and Accountability are being practiced by HONEYSWEET Bakeshop, (3) determine the effects of social responsibility and Accountability on the customers of HONEYSWEET Bakeshop and (4) identify measure to improve the practice of Social Responsibility and accountability of HONEYSWEET Bakeshop. There were six respondents in the study. The findings of the study revealed that most of the respondents are 40 years old and above, single and completed their high school and college educaion. The research design used in this study is the descriptive research method. The study found out that management of HONEYSWEET Bakeshop views Social Responsibility and Accountability as an obligation and duty of one's action to the community. These are being practiced through burning and disposing properly all waste materials and by implementing programs that contribute to the betterment of the society. The study also revealed that Social Responsibility and Accountabilty provide more customer loyalty, build good image for the bakeshop and give edge over competitors.